(untitled) (Global Journal of Human-Social Science, 2013)
Handbook on Procedures for Bullying or Harassment Disputes" elaborated by the authors within the activities of the Basque Observatory on Bullying, an association composed of different kind of professionals: judges, lawyers, labour inspectors, psychologists and doctors.